First office at Masjid Bunder - Reliance Industries Limited (2022)
The Reliance Commercial Corporation office at Masjid Bandar was a 500 sq. ft space rented for Rs.150. The office was shared with a doctor's clinic, separated by a wooden partition. It only had one desk, two chairs, and a telephone, which was shared between Shri Dhirubhai Ambani and the doctor.